IP-Light Technologies Gen 2: Intervention Tools on IPLT for Trauma, Phobia, and Psychological Problems - Ifdil, Ifdil; Fadli, Rima Pratiwi; Zola, Nilma; Ismail, Izwah Binti; Hadi, M Fahli Zatra (Society of Visual Informatics, 2023)
As the fourth industrial revolution guides humanity toward the next stage of civilization, there have been various changes across multiple domains of life. The youngest generations now face a new era in which unexpected problems continuously arise and evolve. Consequently, innovation is needed, especially in psychology and technology. This innovation is important because of the increasing number of issues that plague human life, especially psychological problems, trauma, and phobias. However, modern psychology has not kept pace with these developments. Based on this, the researchers developed a tool called IP-Light Technologies. This tool was developed using a research and development approach. Product testing in the form of prototypes is limited and widely carried out in West Nusa Tenggara, West Sumatra, DKI Jakarta, and Bali. As a result of testing, the final prototype was widely produced. The perceptual light prototype comprises a set of lamps and a multiplicity of LED lights extending in horizontal wings spaced concerning the main handle; an elongated handle extending from the main handle in the opposite direction, vertically to horizontally; a linear array of illuminated displays located on the display surface of the handle; and numerous control switches mounted on the casing. The device further comprises a power supply, and control circuit wherein the LEDs on both wings are arranged in an array configured so that the combination of each bulb may project high-intensity light. A lamp clip with a spring design can be clipped on the edge of a table or any other surface.